Bryophytes and lichens in 16th-century herbaria. (3rd April 2018) - Stech, Michael; van Andel, Tinde; Aptroot, André; Bertin, Alice; Stefanaki, Anastasia
Abstract : The diversity of bryophyte and lichen collections in 9 of the oldest preserved herbaria (dating from ca 1542 to 1577) was compared, including the first reports of bryophytes and lichens from the 'En Tibi' herbarium (possibly 1542–1544) and the herbarium of Leonhard Rauwolf (1560–1563). Bryophytes and lichens formed only a minority in each herbarium compared to the numbers of vascular plant specimens; numbers ranged from representatives of 21 genera in the herbarium of Ulisse Aldrovandi to the single genus Conocephalum in the Rauwolf herbarium. The focus was on large, handsome species of bryophytes and macrolichens, apart from small amounts of additional species collected as 'by-catch' in mixed collections. All herbaria together included 34 genera of bryophytes (36 species and 10 specimens identified to genus level) and 13 genera of lichens (24 species and 4 specimens identified to genus level). The diversity of mosses was higher than that of liverworts, and pleurocarpous mosses were more diverse than acrocarpous mosses. The collectors probably aimed at selecting material that was either characteristic of the vegetation in the respective areas of collecting or used for certain purposes (or both). The former hypothesis is supported by the small overlap in taxonomic diversity between the herbaria, and the latter by the fact that several moss, liverwort, and lichen genera are included whose traditional uses are well documented.